ANALYSIS OF THE ROLE OF TRADITIONAL ADVERTISING AND PR ACTIVITIES IN THE MARKETING COMMUNICATIONS SYSTEM - Чичуліна, Ксенія; Добрянська, Вікторія (SWorldJournal, 2026)
Analysis of the theoretical foundations of PR activities showed that public relations is a strategic communication tool aimed at forming and maintaining mutually beneficial relationships between an organization and various groups of the public. Unlike tra